Second Review of the Implementation of Government Finance Statistics Framework to Strengthen Fiscal Analysis. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
This paper reports on the further developments since 2013 in the implementation of the 2010 Board decision concerning Government Finance Statistics (GFS) to Strengthen Fiscal Analysis, and develops a path to continued improvement of fiscal data in the Fund. The Board decision approved (i) developing a staggered migration strategy, including tailored capacity development inside and outside the Fund taking into consideration country-specific and fiscal surveillance needs; (ii) encouraging staff to continue the effort to routinely assess financial balance sheets during surveillance; (iii) gradually expanding the coverage of fiscal data, taking into consideration country-specific circumstances and fiscal risk assessments; and (iv) reaffirming the support for the phased implementation of the GFS over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet